ЕXPERT EXAMINATION AT THE STAGE OF PREPARATION OF CIVIL CASES FOR JUDICIAL PROCEEDINGS (VERITAS LEGIS JOURNAL, 2026)
A large and very important part of civil proceedings is the preparation of civil cases for trial. The court and the participants in the process perform a variety of preparatory actions in order to form evidence. Among the preparatory actions, the appointment of an expert examination stands out, which takes place in all cases where the need for an expert opinion arises from the circumstances of the case and the evidence presented. In this regard, it is necessary to dwell on some of the problems of the stage of preparing a case for trial, the preparatory hearing as part of the stage of preparing a case, and individual issues of appointing an expert at this stage of civil proceedings.
Keywords: civil process; stage of civil proceedings; preparation of a case for trial; preparatory meeting of the case preparation stage; examination; types of examinations; appointment of an examination